Didelphys uterus: misleading as ovarian cyst (Bangladesh Medical Journal Khulna, 2013)
Mullerian duct anomalies are not uncommon. Anomalies may be diagnosed in infancy, adolescene or young adulthood. Female patient may present with a mass resulting from mucocolpos, haematocolpos, haematometra or primary amenorrhoea, delayed menarche, infertility and repeated pregnancy loses. A 14 years unmarried girl came with lower abdominal pain and mass with severe dysmenorrhoea with a history of lower abdominal surgery 5 months back. Clinically it was diagnosed as ovarian cyst but after laparotomy it was detected didelphys uterus. Left uterus was non-communicated with vagina forming haematometra. Right uterus well developed with one tube and healthy ovary. DOI: http://dx.doi.org/10.3329/bmjk.v45i1-2.13627 Bang Med J (Khulna) 2012; 45 : 30-32